Зимостійкість та морозостійкість Albizia julibrissin Durazz в умовах м. Херсона - Boiko, T.О.; Boіko, P.М.; Sichna, J.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to analyse of resistance to cold and frost-resistance of Albizia julibrissin Durazz in the conditions of Kherson. Material and methods. For the estimation of bioecologycal properties of A. julibrissin was used scale of resistance to cold of Je. Volf, in interpretation of B. Kozlovskiy with coauthors. The final point of frost-resistance settled accounts as the average of this property, shown in points. Results. It is set that brief declines of temperature of air in Kherson in a range –15,0 … –22,1 °С result in the partial damage of plants of albizia, but next vegetation season there is renewal anymore 70 copies. In the investigational terms of A. julibrissin proves as a poorly carrying a winter plant (2 points). However, the results of supervisions specify on the positive dynamics of adaptation of plants to the terms to Kherson, the percent of plants that experience a critical period without substantial damages and able to flower and bear fruit increases, id est prove as middling carrying a winter (3 points) and winter-proof (4 points) plants. It is educed that damage and death of plants during a winter period also related to the unsteady snow-cover, high winds that strengthen the action of subzero temperatures, and ice up branches, that on territory of research can appear several times during a winter. Conclusion. The results got during research ground for more wide distribution of A. julibrissin in Kherson.